Highly Stable Aggregation‐Induced Emission‐Functionalized Histatin1 Coated With Platelet Vesicles for Diabetic Wound Healing - Xiaoxuan Lei; Judun Zheng; Xu Chen; Liwen Liang; Zhuohong Li; Cancan Huang; Minghai Zhao; Gang Wu; Yuhui Liao; Bin Yang (Aggregate)
ABSTRACT The healing of diabetic wounds is primarily hindered by persistent inflammation and excessive oxidative stress, increasing the risks of amputation and sepsis. Strategies based on bioactive substances, including recombinant growth factors and histatin proteins (Hsts), have been shown to promote skin‐related cell migration, anti‐inflammation, angiogenesis, and collagen deposition; however, their long‐term stability remains a challenge. Herein, a platelet membrane‐coated nanoparticle (PNP) system is proposed to achieve enhanced retention of aggregation‐induced emissive (AIE) molecular‐modified Hst1 (Hst1‐AIE@PNPs) for more efficient repair of diabetic wounds. The Hst1‐AIE@PNPs can not only protect Hst1 from degradation in the wound microenvironment but also permit visual monitoring of the controlled release of Hst1 through enhanced fluorescence in the enriched site. Combined with the antioxidant and anti‐inflammatory properties of Hst1, Hst1‐AIE@PNPs can effectively adsorb inflammation‐related factors and further promote re‐epithelialization and collagen deposition, thus achieving high‐quality wound repair. The results highlight the potential of highly stable aggregation‐induced‐emission‐functionalized Hst1 coated with platelet vesicles as a therapeutic platform to promote diabetic wound‐related tissue restoration processes.